The Impact of Fibromyalgia in Spondyloarthritis: From Classification Criteria to Outcome Measures - Alunno, Alessia; Carubbi, Francesco; Stones, Simon; Gerli, Roberto; Giacomelli, Roberto; Baraliakos, Xenofon (Frontiers in Medicine, 2018)
Fibromyalgia (FM) is the most common diagnosis in patients complaining of chronic diffuse pain with fatigue and may occur alone or associated with chronic inflammatory diseases. The prevalence of FM ranges from 2 to 8% in the general population and it can reach up to over 50% in patients with other rheumatic and musculoskeletal diseases (RMDs). Over the last decade, an increasing body of evidence described the impact of FM in patients with spondyloarthritis (SpA) highlighting a number of pitfalls for correct classification, appropriate differential diagnosis and assessment of outcome measures in either conditions. This review article provides an overview of currently available data with regard to the coexistence and reciprocal features of FM and SpA.